Reliable Determination of Ge in Solid Environmental Samples Using a Chemical Preparation Procedure Developed for Si Isotopes and ICP‐MS Analysis. Issue 1 (26th December 2017) - Delvigne, Camille; Angeletti, Bernard; Guihou, Abel; Basile‐Doelsch, Isabelle; Meunier, Jean‐Dominique
Abstract : Germanium (Ge) exists at trace levels in the Earth's crust and is a powerful geochemical tracer of the silicon (Si) cycle. This study proposes a simple and reliable method for determining Ge contents in environmental samples using ICP‐MS. As Si and Ge have very similar chemical properties, we investigated the applicability of the chemical preparation procedure developed for Si isotopes for the determination of Ge in environmental samples. Advantages of this procedure are as follows: (a) efficient removal of the matrix and main interferences affecting Ge determinations by ICP‐MS, (b) a low limit of detection (6 ng l −1 ), (c) relative repeatability of approximately 3% obtained on 74 Ge and (d) robustness and accuracy based on agreement within errors with the published Ge values for rock reference materials (BHVO‐2, AGV‐2 and BCR‐2). This procedure allowed revision of the Ge values of three soil reference materials (1.67 ± 0.09 μg g −1, 2.41 ± 0.18 μg g −1, 1.89 ± 0.10 μg g −1 for GBW 07401, GBW 07404 and GBW 07407, respectively) and proposal of a value for the plant reference material ERM‐CD281 (70 ± 3 μg g −1 ). This method provides a convenient procedure for determining Ge mass fractions in environmental samples and opens the possibility of coupling two tracers of the Si biogeochemical cycle with a single measurement procedure. Key Points: Reliable determination of Ge mass fractions by ICP‐MS Two Si cycle tracers (Si isotopes and Ge/Si ratio) in one chemical preparation. Revision of the Ge content of three soil RMs (GBW 07401, 07404, 07407).